New species of Bidessonotus Régimbart, 1895 with a review of the South American species (Coleoptera, Adephaga, Dytiscidae, Hydroporinae, Bidessini) - Miller, Kelly B. (Zookeys, 2016)
Abstract. The South American species of the New World genus Bidessonotus Régimbart, 1895 are reviewed with descriptions of seven new species. This brings the total number of valid Bidessonotus species to 37, making it the largest Bidessini genus in the New World. The new species are Bidessonotus annae sp. n. (Venezuela), Bidessonotus josiahi sp. n. (Venezuela), Bidessonotus palecephalus sp. n. (Venezuela), Bidessonotus reductus sp. n. (Venezuela), Bidessonotus septimus sp. n. (Venezuela), Bidessonotus spinosus sp. n. (Venezuela), and Bidessonotus valdezi sp. n. (Guyana, Suriname). New distribution records are provided for many other South American Bidessonotus species. The main diagnostic features of Bidessonotus species are in the male genitalia, and these are illustrated for all South American species. Diagnostic features, distributions (including distribution maps), and additional comments are provided for all South American species.